The Relationship of Mother Characteristics and Childhood Nutrition Status to the Rough Motor of Toddlers 3-5 Years Old - Susanti, Erna Evi (Sport and Nutrition Journal, 2023)
Toddlers aged 3-5 years are at an ideal period in the development process, especially in gross motor development. Gross motor skills are toddlers' ability to move by involving body structures and functions. The gross motor skills of toddlers can be influenced by several factors, namely maternal characteristics and nutritional status. The features of mothers involved in gross motor include knowledge, education, employment, and mother's care. It is also a factor in the nutritional status of children, so it will indirectly be connected to the child's motor. This study used a cross-sectional design with purposive sampling techniques; the study sample comprised 37 respondents from toddlers and their mothers. The research was conducted at the Children's Poly, Kartika Pulomas Hospital, East Jakarta. The data measured were toddlers' nutritional and gross motor status using the DDST screening format. The characteristics of respondents in the normal gross motor category were 16 toddlers (43.2%), while toddlers with suspected gross motor were 21 toddlers (56.8%). The bivariate analysis results showed that knowledge, maternal parenting, and nutritional status had a significant relationship with gross motor with a p-value of < 0.05. Age, education, and occupation had no association with gross motor with p-value > 0.05.